FRI0099 Prevalence of Heart Failure in Rheumatoid Arthritis is Doubled in Remission yet Quadrupled in Active Disease. (10th June 2014) - Schau, T.; Gottwald, M.; Butter, C.; Zaenker, M.
Abstract : Background: Risk of heart failure (HF) is increased in patients with rheumatoid arthritis (RA) and the predominantly prevalent type is diastolic HF with normal ejection fraction (HFNEF). Traditional cardiovascular risk factors are overrepresented in RA but chronic inflammation is an independent significant contributor to myocardial dysfunction. However, there is great variance in reported prevalence of HF in RA due to differing diagnostic standards and HFNEF is apparently underestimated. Objectives: To determine prevalence of heart failure in a community-based RA-cohort compared to age- and gender-matched controls using the 2008 European Society of Cardiology (ESC) diagnostic guidelines. Methods: A prospective cross-sectional study including 157 consecutively recruited RA-patients from our outpatient clinic during a 3 months period. Inclusion criteria were written consent and diagnosis of RA fulfilling ACR/EULAR-criteria. Blinded to any health information an age- and gender-matched control group (n=77) was recruited from a district office and veterans of our hospital staff. Demographic and clinical data were obtained using standardized questionnaire and evaluation of Framingham criteria. Lab tests included NT-proBNP (Roche). Echocardiography of all subjects contained tissue doppler and strain imaging. Results: The cohorts were comparable in gender distribution (67% vs. 69% females) and age (mean (SD) 61 years (±13) vs. 59 (±12). RA median DAS28 was 2.8 (Interquartile range (IQR) 2.0-3.4), median HAQ 1.1 (IQR 0.8-2.0) with remission (DAS28<2.6) in 45%, mild disease activity (DAS28 2.6-3.2) in 25% and higher disease activity (DAS28>3.2) in 30%. Prevalence of HF was significantly higher in RA vs. controls (38 (24%) vs. 5 (6%), p<0.001). Of all diagnosed HF, only 2 RA patients showed reduced ejection fraction. Significantly more RA patients reported on dyspnea on exertion (DOE, 66 (44%) vs. 14 (19%), p<0.001). RA patients showed significantly higher mean BMI 29 (±5) vs. 27 (±4), p<0.001 and higher prevalence of hypertension (59% vs. 40%, p=0.019). No significant differences were found for diabetes type 2 (13% vs. 8%), chronic kidney disease (GFR<60ml/min; 15% vs. 6%) and coronary artery disease (8% vs. 3%). Analyzing age decades, HF was found 10 years earlier and always more often in RA patients. Subgroup analysis revealed highest prevalence of HF in higher disease activity (37%, RR 5.7, p<0.001 compared to controls), 30% during mild disease activity (RR 4.6, p=0.0015) and 13% during remission (RR 1.95, p=0.264). In multivariate analysis adjusted for age and gender, remaining risk factors for HF in RA were DAS28≥2.6 (OR 3.4, 95%CI 1.3-9.8), RA-duration>10years (OR 2.6, 95%CI 1.2-5.8), CRP median>10mg/l (OR 4.8, 95%CI 1.1-21), and ESR>16mm/h (OR 5.4, 95%CI 2.1-16). Conclusions: According to ESC guidelines, HF was found elevated 4-6fold in active RA and 2fold increased still in states of controlled disease. Heart failure with normal ejection fraction i.e. of diastolic type is found in as many as a quarter of all RA patients. DOE is obviously related to other causes. We conclude that optimal control of RA and awareness for HFNEF are crucial for adequately addressing HF in RA patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3746